ANALISIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN PAI DI MTS NEGERI 02 BATAM - Siti Uswah; Sahrial Nauli; Syarifah Raudatunnur; Rosdianah; Zulkifli Halim Busra; Elvika; Sabrun Jamil (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study is motivated by the existence of learning difficulties experienced by students in Islamic Religious Education (PAI) at MTs Negeri 02 Batam, which have an impact on students’ understanding and learning outcomes. Learning difficulties in PAI need to be analyzed comprehensively in order to identify appropriate solutions. The purpose of this study is to analyze the forms of students’ learning difficulties in PAI subjects and to identify the factors influencing these difficulties. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of eighth grade students and PAI teachers at MTs Negeri 02 Batam. Data were collected through observation, interviews, and documentation. The data analysis was conducted through data reduction, data display, and conclusion drawing. The results of the study indicate that students experience various learning difficulties, including difficulties in understanding conceptual and memorization based materials, low learning motivation, lack of interest in PAI lessons, and limited variation in teaching methods. In addition, internal factors such as cognitive ability and learning motivation, as well as external factors such as the learning environment and instructional strategies used by teachers, contribute to students’ learning difficulties. Therefore, the implementation of more innovative and student-centered learning strategies is needed to reduce students’ learning difficulties in Islamic Religious Education.